Illuminating the Regulatory Dynamics of Plant Growth: A Study on Cell Cycle Genes and Motif Enrichment in Arabidopsis thaliana - Wang, Xuesong; Justus Liebig University Giessen (My University, 2024)
Plant growth and development rely on the proliferation and expansion of root tip cells, which involves a network of genes participating in the regulation of the cell cycle, namely the mitotic cell cycle and endocycle. Since plants have their sessile nature, they cannot actively avoid adverse factors imposed by the environment, compelling them to develop a suite of adaptive mechanisms to enhance their adaptability and ensure survival. Some of these adaptive mechanisms influence the regulation of the cell cycle, although the underlying mechanistic connections remain elusive. Including the role of transcription factors in regulating the expression of cell cycle genes and their influencing factors, as well as the regulation of the transition between the mitotic cycle and endocycle, remain current research challenges. Research on plant cell cycle genes reached its peak in the early 21st century when combining cell cycle synchronization in cell cultures with DNA microarray and other technologies. At that time cycle-related genes have been assigned to different cell cycle phases. However, since then, the cell cycle gene networks have hardly been studied or annotated in more detail. Moreover, the ramifications of cell cycle synchronization on the cell cycle dynamics are not fully characterized and quantified. To this end, this work aimed to map and analyze cell cycle gene networks, leveraging more advanced technologies and methodologies, such as single-cell sequencing, to undertake a comprehensive exploration of the cell cycle networks. As for transcriptional regulation mechanisms of cell cycle genes, the focus has primarily been on the issue of transcription factor binding under single motif conditions. This work will focus on the binding characteristics of motif pairs and their role in transcriptional regulation. This work integrated root single-cell and bulk sequencing data of *Arabidopsis thaliana* to calculate correlations, delineating developmental zones at the single-cell level. Cycling cells in these zones were identified using known cell cycle genes and clustering methods. Differential expression analyses on cells in different cycle phases expanded the cell cycle-related gene set. The Paired Motif Enrichment Tool (PMET) identifies promoter motif pairs. Building on the existing PMET foundation, this work extends its application to uncover genetic mechanisms regulating the mitotic cycle and endocycle. Using PMET, diverse promoter motif pairs linked to cell cycle-related and stress-induced genes were identified, elucidating gene regulatory patterns involving synergistic transcription factors. Many motif pairs are specific to genes in certain cycle phases and stress conditions, offering new insights into the regulatory mechanisms of cell cycle and stress-induced gene networks.
Keywords: Cell Cycle Regulation; Transcriptional Networks; Motif Pair Analysis; Single-Cell Sequencing; Root Development; ddc:570